Assessment of PAX1 and JAM3 methylation triage efficacy across HPV genotypes and age groups in high-risk HPV-positive women in China - Liang, Hui; Liu, Yao; Yin, Suyue; Jiang, Mengyu; Dou, Qiuyan; Wang, Hanhan; Liu, Jie; Chen, Yibo; Liu, Pei; Wang, Jing; Wang, Yishan; Wu, Zhe (Frontiers in Oncology, 2024)
ObjectiveThis study aimed to evaluate the clinical utility of PAX1/JAM3 methylation (CISCER) test in triaging high-risk human papillomavirus (hrHPV)-positive women.MethodsWe enrolled women who underwent opportunistic screening at Cervical Disease outpatient clinics of Xuzhou Maternity and Child Health Hospital, and Yueyang Central Hospital from December 2022 to May 2024. The effectiveness of CISCER and cytology tests in triaging hrHPV+ patients was analyzed.ResultsAmong the 436 study participants, 283 (64.9%) had no cervical intraepithelial neoplasia (CIN), while 53 (12.2%) had CIN1, 40 (9.2%) had CIN2, 34 (7.8%) had CIN3, and 26 (5.9%) had cervical cancers. The CISCER tests identified all cases of cervical cancer, particularly 2 hrHPV-negative adenocarcinoma cases. In 396 hrHPV+ individuals, the sensitivity of CISCER tests for detecting CIN2+ lesions was 92.6% (95% CI: 87.2-97.9%), with a specificity of 95.7% (95% CI: 93.4-98%), and an area under the receiver operating characteristic curve (AUC) of 0.941 (95% CI: 0.903-0.979), outperforming cytology tests in both HPV16/18+ and non-16/18 hrHPV+ women. Notably, CISCER demonstrated 100% (95% CI: 90-100%) sensitivity in women aged≥50 and 100% (95%CI: 93.6-100%) specificity in women aged<30. Among CIN2+ women, 37.2% (including 3 cancer) showed low-grade cytological changes that could be detected by CISCER. Meanwhile, 52% of CIN2- women exhibited cytological abnormalities but had negative CISCER results. The immediate CIN3+ risk based on positive CISCER results was 54% (95% CI: 43.8-63.9%).ConclusionThe PAX1/JAM3 methylation detection using cervical exfoliated cells showed superior triage performance for hrHPV-positive patients compared to traditional strategies.